2017
DOI: 10.15845/bells.v7i0.1107
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the CORYL Corpus: What it Is and How We Can Use it to Shed Light on Learner Language

Abstract: This article presents coryl (CORpus of Young Learner language), and demonstrates how the corpus can help reveal or shed further light on many phenomena which are manifested in the written English language of Norwegian school pupils. The paper begins with an introduction of coryl, then focuses on learner language and the role of corpora in the study of this. The following sections are devoted to what we term Computer-aided Error Analysis and Interlanguage Analysis (not involving errors). Within these sections, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…11 -12 year-old learners, for example, almost exclusively used the two tenses present simple and present continuous while older learners used a wider range of verb tenses (Lasagabaster & Doiz, 2003). Hasselgreen and Sundet (2017) made a similar observation. In a brief analysis of texts from the CORYL corpus (corpus of young learner language), they found that learners at the CEFR level A1 tended to mainly use the verb 'was' to express the past tense.…”
Section: Grammar: Syntax and Morphologymentioning
confidence: 67%
See 2 more Smart Citations
“…11 -12 year-old learners, for example, almost exclusively used the two tenses present simple and present continuous while older learners used a wider range of verb tenses (Lasagabaster & Doiz, 2003). Hasselgreen and Sundet (2017) made a similar observation. In a brief analysis of texts from the CORYL corpus (corpus of young learner language), they found that learners at the CEFR level A1 tended to mainly use the verb 'was' to express the past tense.…”
Section: Grammar: Syntax and Morphologymentioning
confidence: 67%
“…Further cohesive devices found in the texts were, for example, temporal conjunctions (e. g. first), hyponymy (the use of specific and general words from the same semantic field, e. g. banana/fruit), adversative conjunctions (e. g. but), demonstratives (e. g. this) and comparatives (e. g. more) (Yasuda, 2019). Hasselgreen and Sundet (2017), in a corpus analysis of young Norwegian EFL learners' texts, found considerable differences regarding the use of conjunctions between 12 / 13 and 15 / 16 year-old learners. Several conjunctions and adverbial conjuncts (however, since, even if, although, even though and therefore), which were sometimes used by the older learners, almost never appeared in younger learners' texts (Hasselgreen & Sundet, 2017, p. 210).…”
Section: Coherence and Cohesionmentioning
confidence: 99%
See 1 more Smart Citation
“…They documented the development of performance descriptors and the development of an international vocabulary corpus for young EFL learners. Moreover, researchers also reported the development of regional corpora for young EFL learners (Hasselgreen & Sundet, 2017; Sundh, 2016). As young learner corpora are increasingly available, corpus-based studies are on the rise in order to understand the development of young EFL learners’ English skills (Jiang et al., 2019; Seog & Choi, 2018).…”
Section: From Infancy To Adolescence: a Burgeoning And Increasingly Diverse Fieldmentioning
confidence: 99%
“…Very little research has been done on lower secondary pupils' (age 13-16) writing in general (cf. Hasselgren & Sundet, 2017) and on formality level in particular (but see Thomson, 2018). Also, little is known about what instructions pupils are given regarding formality level.…”
mentioning
confidence: 99%